UPAYA PENINGKATAN HASIL BELAJAR MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA MATAPELAJARAN IPAS DI SDN 34 PALEMBANG - Melani safitri; Kurnia , Kurnia; Yuliana, Lisa; Monalisa, Monalisa; Adim, Muhammad; Wiyono, Ketang (Cerdas Proklamator, 2024)
This study aims to improve student learning outcomes in Natural and Social Sciences (IPAS) subjects in elementary schools by using the problem based learning (PBL) learning model. The research method used by researchers is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. The research subjects consisted of 30 students of class V.A at State Elementary School 34 Palembang. The results showed that the implementation of PBL improved students' learning outcomes, as seen from the gradual increase in students' average scores in each cycle: pre-cycle (61.3%), cycle I (64.4%), and cycle II (83.4%). This finding confirms that PBL is an effective learning model to improve learning outcomes in IPAS subjects at the primary school level.